Investigation of molecular aggregation mechanism of glipizide/cyclodextrin complexation by combined experimental and molecular modeling approaches - Tianhe Huang; Qianqian Zhao; Yan Su; Defang Ouyang (Elsevier, 2019)
Cyclodextrin complexation is a wise strategy to enhance aqueous solubility of water-insoluble drugs. However, the aggregation mechanism of drug-cyclodextrin complexes is still unclear. This research aimed to investigate the molecular aggregation mechanism of glipizide/cyclodextrin complexation by the combination of experimental and modeling methods. Binding free energies between glipizide and cyclodextrins from modeling calculations were higher than those by the phase solubility diagram method. Both experimental and modeling results showed that methylated-β-cyclodextrin exhibited the best solubilizing capability to glipizide. Size-measurement results confirmed the aggregation between glipizide and all four cyclodextrins in high concentrations. Glipizide/γ-cyclodextrin and glipizide/β-cyclodextrin complexes showed stronger aggregation trend than HP-β-cyclodextrin and methylated-β-cyclodextrin. The substituted groups in the rim of HP-β-cyclodextrin and methylated-β-cyclodextrin lead to weak aggregation. This research provided us a clear molecular mechanism of glipizide/cyclodextrin complexation and aggregation. This research will also benefit the formulation development of cyclodextrin solubilization. Keywords: Glipizide, Cyclodextrin, Molecular modeling, Aggregation, Molecular mechanism